PAYMENT FOR ECOSYSTEM SERVICES: A TOOL FOR SUSTAINABLE FOREST MANAGEMENT - Thai, Aom; Chai, Nong; Chai, Som (Journal of Selvicoltura Asean, 2025)
The rapid depletion of forest ecosystems worldwide has led to an increasing need for sustainable forest management practices. One promising approach to incentivize conservation efforts is the implementation of Payment for Ecosystem Services (PES) programs. PES aims to financially reward individuals or communities who provide ecological services, such as maintaining forest cover, conserving biodiversity, and improving water quality. Despite growing interest in PES, its effectiveness as a tool for sustainable forest management remains an area of active research. This study aims to evaluate the effectiveness of PES programs in promoting sustainable forest management and enhancing the livelihoods of local communities. Specifically, the research examines the impact of PES on forest conservation practices, economic benefits for participants, and the long-term sustainability of forest ecosystems. A mixed-methods approach was used, combining both qualitative and quantitative data. Surveys were conducted with 150 households involved in PES programs across three forest regions. In-depth interviews with local stakeholders, including forest managers, government officials, and community leaders, were also carried out. Data was analyzed using descriptive statistics and thematic analysis to assess the outcomes of PES programs. The findings suggest that PES programs have led to increased forest conservation efforts, improved local livelihoods, and greater awareness of ecosystem services. However, challenges such as inadequate funding, lack of technical support, and limited participation of marginalized groups were identified as barriers to full program effectiveness. PES programs can be a viable tool for sustainable forest management, provided that they are properly funded, inclusive, and supported by strong governance frameworks. Long-term success will depend on overcoming existing challenges and ensuring equitable participation.